Remodelagem de uma usina sucroalcooleira para incremento da cogeração de energia com aproveitamento do palhiço - Lacerda, Kaito Arnoni [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Due to the current environmental policies applied to the sugar and ethanol industry, which propose the prohibition of the canebrake burning act, tons of biomass in the form of sugarcane trash are being left on the field. Thus, in a reality of potential energy crisis in the country and pursuit of sustainable alternatives on the energy generation, the bioenergy suits as an important solution for this market and, therefore, the energy potential of the sugarcane trash comes to be investigated as an additional source at the power cogeneration plants. In this context, this work proposes a study for the viability of solutions which aim a more useful end to the sugarcane trash in an established and operating sugarcane mill in São Paulo state, generating, then, greater electricity surpluses in both harvest and interharvest seasons. In order to provide evidences for the viability of each solution, thermodynamic, thermoeconomic and economic inquiries were applied. Five adjustment proposals of the cogeneration plant were analyzed, wherein, four of them were modified and improved in the already established plant, whilst for the other one, the implantation of an adjunct cogeneration plant, fuelled solely by sugarcane trash, was suggested. Among the studied solutions, in addition to confirming the sugarcane trash's high potential as an increment for the extra electricity production, it was possible to obtain, in some cases, an inferior electricity cost compared to the one verified in the previous operational plant. However, by means of the economic analysis, it was ascertained that the current electricity price policy applied to the Brazilian electric market, with frequently lower prices compared to the ones needed to guarantee the return of the investments on the installed capacity expansion, lack of tax incentive and subsidy to the sector are still impediments for the viability of new projects

Em decorrência das atuais políticas ambientais aplicadas ao setor sucroalcooleiro, que propõem a proibição da prática da queima dos canaviais, toneladas de biomassa na forma do palhiço da cana-de-açúcar estão sendo deixadas no campo. Assim, em uma realidade de potencial crise energética no país e busca de alternativas sustentáveis na geração de energia, a bioenergia torna-se uma importante solução para este mercado e, portanto, o potencial energético do palhiço passa a ser investigado como um adicional nas centrais de cogeração de energia. Neste contexto, este trabalho propõe um estudo da viabilidade de soluções que visam o aproveitamento do palhiço da cana-de-açúcar em uma usina sucroalcooleira instalada e em operação no estado de São Paulo, gerando, assim, maiores excedentes de eletricidade tanto na safra quanto na entressafra. A fim de fornecer indícios da viabilidade de cada uma das soluções, foram empregadas investigações de caráter termodinâmico, termoeconômico e econômico. Cinco propostas de adequações da planta de cogeração foram analisadas, sendo que, em quatro delas, foram realizadas modificações e melhorias na planta já instalada, enquanto em um caso foi proposta a inserção de uma planta de cogeração paralela alimentada exclusivamente por palhiço. Dentre as soluções analisadas, além de se confirmar o elevado potencial do palhiço para incremento da produção de excedentes de eletricidade, foi possível obter em alguns casos um custo de eletricidade inferior aquele verificado atualmente na planta em operação. Entretanto, através da análise econômica constatou-se que a atual política de preços de venda de eletricidade aplicada ao mercado elétrico brasileiro, com valores frequentemente inferiores àqueles necessários para garantir o retorno de investimentos em ampliação da capacidade instalada, falta de incentivos fiscais e subsídios...
Keywords: Energia eletrica e calor - Cogeração; Biocombustíveis; Açucar - Usinas; Bagaço de cana; Biomass energy